Inequality in education: Evidence for Latin America - Guillermo Cruces; Carolina García Domench; Leonardo Gasparini (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This paper provides original empirical evidence on the evolution of education inequality for the Latin American countries over the decades of 1990 and 2000. The analysis covers a wide range of issues on the differences in educational outcomes and opportunities across the population, including inequality in years of education, gaps in school enrolment, wage skill differentials and public social expenditure. The evidence indicates a significant difference between the 1990s and the 2000s in terms of both the assessment of the equity of the education expansion and its impact on the income distribution. In particular, changes in the 2000s seem to have had an equalizing impact on earnings, given the more pro-poor pattern of the education upgrading and a more stable or even increasing relative demand for low-skill labour.
Keywords: I24; I25; I28; O15; 330; education; inequality; enrolment; wage premium; Latin America; Bildungsertrag; Bildungsverhalten; Bildungsniveau; Einkommensverteilung; Lateinamerika